2013
DOI: 10.1371/journal.pone.0055245
|View full text |Cite
|
Sign up to set email alerts
|

Isoenergetic Replacement of Fat by Starch in Diets for African Catfish (Clarias gariepinus): Effect on Water Fluxes in the Gastro Intestinal Tract

Abstract: The effect of an isoenergetic replacement of dietary fat by starch, on chyme characteristics and water fluxes in the gastro intestinal tract (GIT) was assessed. Adult African catfish (Clarias gariepinus) were fed a starch (SD) or fat (FD) diet and groups of fish were dissected at 2, 5 and 8 h after the consumption of a single meal. Chyme was collected quantitatively and was analysed for osmolality and dry matter (DM) content. Postprandial water fluxes were calculated, while using yttrium oxide (Y2O3) as an ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 19 publications
4
19
0
Order By: Relevance
“…The results for chyme DM content have been previously reported (Harter et al . ). A significant ( P < 0.05) diet effect on chyme viscosity was observed in the stomach and distal intestine, but not in the mid‐intestine.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The results for chyme DM content have been previously reported (Harter et al . ). A significant ( P < 0.05) diet effect on chyme viscosity was observed in the stomach and distal intestine, but not in the mid‐intestine.…”
Section: Resultsmentioning
confidence: 97%
“…The obtained results on the postprandial water fluxes in the GIT of African catfish are discussed in more detail by Harter et al . (). Results suggest that animals fed FAT had a higher average chyme DM in the stomach ( P < 0.002) compared to STARCH.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Leenhouwers et al (2007b) showed a decrease in faecal dry matter with increasing dietary viscosity as a result of replacing different ingredients in African catfish and that influenced the removal of the faeces. In addition, there are some studies (Leenhouwers et al, 2007a;Harter et al, 2013) which observed that the variation in the characteristics of chyme related to the faecal characteristics.…”
Section: The Quantity and Quality Of Faecal Waste And Related Studiesmentioning
confidence: 99%
“…Also, the requirement for water for fat emulsification may play a role, since viscous substances are known to bind water. However in Nile tilapia (Amirkolaie et al, 2006), African catfish (Harter et al, 2013) and also in striped catfish (Tran-Tu et al, 2019, submitted article) it has been shown that the viscosity of the chyme increase as it passages towards the distal intestine.…”
Section: Digestibility and Performancementioning
confidence: 99%